The Role of Pencak Silat in Building Youth Character in Kedung Kendo Village - Nisa, Khoirun; Syahfrilina, Venny Zahra; Masniyah, Hannik; Mardiani, Desika Putri; Susilo, Heryanto (STAI MA'ARIF MAGETAN, INDONESIA, 2025)
Pencak silat is one of Indonesia's original cultural heritages that has high philosophical and character values. This martial art is not only aimed at training physical skills, but also as a medium for character education. Pencak silat not only teaches physical skills, but also contains spiritual and moral aspects that are important in character building. The findings of the study showed that in each training session, there was an emphasis on the importance of values ​​such as honesty, politeness, and responsibility. This study found that participants involved in pencak silat had a higher level of integrity and were more compliant with moral norms in their daily lives. This study aims to describe the role of pencak silat in shaping the character of adolescents. Through participatory observation and in-depth interviews with trainers and participants, it was found that pencak silat not only teaches self-defense techniques, but also noble values ​​such as patience, courage, and sportsmanship. In addition, pencak silat also provides a forum for adolescents to interact socially and develop self-confidence. The results of this study conclude that pencak silat can be an effective alternative in efforts to shape the character of the younger generation.